Transformations of the soul : Aristotelian psychology, 1250-1650 - Perler, Dominik (Brill, 2009)
Focusing on the period between Albertus Magnus and Descartes, the ten contributions examine various Aristotelian theories of the soul. They pay particular attention to the question of how the metaphysical status of the soul and its cognitive functions (sense perception, imagination, intellectual thinking) were explained.